Learning Difficulties of the 5th Grade Elementary School Students in Learning Human and Animal Body Organs - Maryani, I.; Husna, N. N.; Wangid, M. N.; Mustadi, A.; Vahechart, R. (Jurnal Pendidikan IPA Indonesia, 2018)
Natural Science is an elementary school subject that requires students to organize ideas and concepts about the natural world gained from experiences through a series of scientific processes such as investigating, composing, and presenting ideas. The high complexity causes many cases of learning difficulties. This study aims to diagnose the learning difficulties that occur on 5th-grade elementary school students. The research was conducted in Muhammadiyah Pakem Elementary School, Sleman, Yogyakarta Special Regency. The subjects were 29 of 5th-grade elementary students. Data collection techniques were interviews, tests, and documentation. Data analysis techniques were descriptive statistic as a quantitative analysis and interactive model as a qualitative analysis. The learning difficulties were diagnosed by describing the students who were identified having learning difficulties; localizing the difficulties; and determining the factors that cause learning difficulties. The results showed that the difficulties experienced by students were in basic competence 1.1-1.5 (human blood circulation organs). The average percentage of students’ learning difficulties in Basic Competence 1.1 was 48%; Basic Competence 1.2 was 51.1%; Basic Competence 1.3 was 57.6%; Basic Competence. 1.4 is 64.7%; and Basic Competence 1.5 is 53.7%. The highest percentage of learning difficulties was in Basic Competence 1.4 (identifying human circulatory organs). It was caused by the students’ low attention and motivation to learn natural science, the imprecise teaching methods, the parents’ attention, and the negative influence of mass media.